2021
DOI: 10.3390/su132212845
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits That Affect Travel Intentions during Pandemic COVID-19: The Case Study of Serbia

Abstract: The pandemic caused by COVID-19 has enormous effects on peoples’ lives and on the global economy. The outbreak and effects of COVID-19 have resulted in fears, concerns, and anxiety among people all around the world. The aim of this study is to investigate the relationship between the fear of COVID-19, travel anxiety, and travel intention among residents in Serbia. In addition to the above, the aim of the study was to examine the impact of personality traits on the fear of COVID-19, travel anxiety, and travel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 126 publications
1
13
1
Order By: Relevance
“…Tourist personality is expected to influence activity preferences at destinations. Although the influence of individual characteristics has not been analyzed in the context of activity preferences, the expectation of a positive influence is based on the fact that many authors have demonstrated the influence of tourist personality on behavior [15,16,[90][91][92], with some authors clearly highlighting the influence of tourist personality on tourists' choice of activities [93][94][95]. It should also be noted that the Big Five model has not been widely used so far for tourists, but rather, simplified psychographic models have been applied [96].…”
Section: Activity Preferencesmentioning
confidence: 99%
“…Tourist personality is expected to influence activity preferences at destinations. Although the influence of individual characteristics has not been analyzed in the context of activity preferences, the expectation of a positive influence is based on the fact that many authors have demonstrated the influence of tourist personality on behavior [15,16,[90][91][92], with some authors clearly highlighting the influence of tourist personality on tourists' choice of activities [93][94][95]. It should also be noted that the Big Five model has not been widely used so far for tourists, but rather, simplified psychographic models have been applied [96].…”
Section: Activity Preferencesmentioning
confidence: 99%
“…More recently, several studies addressed the impact of personality traits on leisure travel during the COVID-19 pandemic. Sreen et al (2023) explored the interplay of personality traits and motivation in leisure travel decision-making during the pandemic, travel anxiety and the influence on travel intentions (Tepav cevi c et al, 2021). Talwar et al (2022) examined the impact of individuals' personality traits on their leisure travel intentions during and after the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…External stimuli spur one's desire to travel, for example, marketing campaigns, the promotion of destinations et al (Reza Jalilvand et al, 2012). Needs and desires are a set of attributes such as personal attitudes (Mohsin et al, 2017), values, and traits (Tepavčević et al, 2021). External factors include destination image, past travel experience, time, and economic variables (Hsieh et al, 2016;Rasoolimanesh et al, 2021;Yao et al, 2021).…”
Section: Travel Intentionmentioning
confidence: 99%
“…Many researchers have also explored travel intentions in the context of COVID-19 pandemic. For example, Tepavčević et al (2021) found that travel intention and fear of COVID-19 pandemic are influenced by different personality traits. In addition, different fears of COVID-19 (infection during travel, as well as lack of funds, and loss of job during the critical period of COVID-19 pandemic) reduce travel intention (Gajić et al, 2021).…”
Section: Travel Intentionmentioning
confidence: 99%